Pengaruh Manajemen Kurikulum dan Kompetensi Ustaz Terhadap Prestasi Belajar Santri pada Era Milenial di Pondok Pesantren Darul Muqomah Pangandaran - Masud Masud (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to (1) determine the effect of curriculum management on student achievement in Islamic boarding schools at Darul Muqomah Pangandaran, (2) determine the effect of Ustadz competence on student achievement in Darul Muqomah Pangandaran Islamic Boarding School (3) Determine the effect of curriculum management and Ustadz competence on achievement. students study at the Darul Muqomah Islamic Boarding School in Pangandaran. In this study the authors used quantitative descriptive and verification with the type of correlational research. Data were collected through questionnaires from respondents with a population of all teachers (30 teachers) at the Darul Muqomah Islamic Boarding School, Pangandaran. Researchers conducted validity and reliability tests, as well as multiple linear regression through the SPSS windows 24 program. Based on the results of the analysis of research data, that: Islamic boarding school curriculum management, ustadz competence and student learning achievement at the Darul Muqomah Islamic Boarding School, Pangandaran are good. The management of the pesantren curriculum and the competence of the ustadz simultaneously affect the learning achievement of students at the Darul Muqomah Islamic Boarding School in Pangandaran, this is evidenced by the multiple linear regression equation model with a significance value of 0.000 < 0.05, Ho is rejected and Ha is accepted.